Good feeding throughout the year - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Choosing grazing sites, growing forage crops, use of supplements, storing feed as hay and silage, and feeding of housed goats.